A US cost-minimization model comparing ravulizumab versus eculizumab for the treatment of atypical hemolytic uremic syndrome. (1st December 2020) - Wang, Yan; Johnston, Karissa; Popoff, Evan; Myren, Karl-Johan; Cheung, Antoinette; Faria, Claudio; Tomazos, Ioannis
Abstract: Aims: Ravulizumab, engineered from eculizumab, provides sustained C5 inhibition in atypical hemolytic uremic syndrome (aHUS) while reducing dosing frequency (every 8 vs 2 weeks, respectively). Treatment choice often carries significant financial implications. This study compared the economic consequences of ravulizumab and eculizumab for treating aHUS. Materials and methods: A cost-minimization model compared direct medical costs for ravulizumab and eculizumab in treating aHUS, assuming equivalent efficacy and safety, and took a US payer perspective, a lifetime horizon, and a 3.0% cost discount rate. The base case modeled adult and pediatric treatment-naïve populations, with characteristics based on clinical trials, and treatment patterns (duration, discontinuation, re-initiation) derived from eculizumab studies with long-term follow-up. Treatment costs (2019 US) were based on wholesale drug acquisition costs, Centers for Medicare & Medicaid fee schedules, and published disease management studies. Sensitivity analyses were conducted by adjusting relevant variables. Results: Ravulizumab provided lifetime per-patient cost reductions (discounted) of 32.4% and 35.5% vs eculizumab in adult and pediatric base cases, respectively. Total costs for ravulizumab vs eculizumab were 12, 148, 748 and 17, 979, 007, respectively, for adults, and 11, 587, 832 and 17, 959, 814, respectively, for children. Pre-discontinuation treatment contributed the largest proportion of total costs for ravulizumab (94.8% and 88.0%) and eculizumab (94.8% and 87.8%) in adults and children, respectively. Across sensitivity analyses, ravulizumab provided cost reductions vs eculizumab. Limitations: The model included several typical assumptions. Base case patients with more severe stages of chronic kidney disease were assumed not to discontinue treatment, nor to experience an excess mortality risk in either treatment arm, which may not reflect real-world clinical observations. Additionally, rebates and discounts on medication acquisition or administration were not considered. Conclusions: In US patients with aHUS, ravulizumab provided cost reductions of 32.4–35.5% vs eculizumab, with a reduced dosing frequency for ravulizumab. The magnitude of reductions was consistent across sensitivity analyses.